Preparation method of high-hardness silicon nitride ceramic

By sintering the silicon source, the titanium source and the carbon source in a nitrogen atmosphere, an intermediate containing titanium nitride and silicon nitride is formed, and mixed with the sintering aid is sintered, the problem of difficult control of the particle size of the second phase and poor wettability is solved, and the preparation of high-hardness silicon nitride ceramics is realized.

CN119751088AActive Publication Date: 2025-04-04SINOMA ADVANCED NITRIDE CERAMICS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510266737.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-04
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

In the prior art, the problem of poor control of the size of the second phase particles, uneven particle dispersion, and poor wettability of the second phase particles and silicon nitride matrix leads to poor performance of silicon nitride hardness.

Method used

By sintering the silicon source, the titanium source and the carbon source in a nitrogen atmosphere, an intermediate containing titanium nitride and silicon nitride was obtained, and mixed with the sintering aid to form a silicon nitride ceramic, and the crystal phase transition between the α- to β phases occurs, and the in-situ synthesized TiN is embedded between the silicon nitride grains.

Benefits of technology

The distribution uniformity of TiN in the silicon nitride grains is improved, the mechanical properties of silicon nitride and the uniformity of the sintered body color are enhanced, the interface bonding force and bonding strength between silicon nitride and the second phase is improved, and the hardness of silicon nitride is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751088A_ABST
    Figure CN119751088A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of silicon nitride materials, in particular to a preparation method of high-hardness silicon nitride ceramic, which comprises the following steps: S1, mixing a silicon source, a titanium source and a carbon source, and sintering in a nitrogen atmosphere to obtain an intermediate; and S2, mixing the intermediate with a sintering aid, and sintering to obtain the high-hardness silicon nitride ceramic. On one hand, the distribution uniformity of TiN in silicon nitride crystal grains is improved through an in-situ synthesis mode, the mechanical property is improved, the uniformity of the color of a sintered body is improved, on the other hand, TiN particles and the silicon nitride crystal grains are generated synchronously, the interface bonding force of silicon nitride and a second phase is improved, and the service life of the silicon nitride ceramic is prolonged. Meanwhile, the interface bonding strength of the silicon nitride and the second phase is enhanced, and the hardness of the silicon nitride is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon nitride materials, and in particular to a method for preparing high-hardness silicon nitride ceramics. Background Art

[0002] Silicon nitride ceramic materials have excellent properties such as high strength, high temperature resistance, oxidation resistance and wear resistance, and can be applied to many scenes with complex conditions and harsh environments. With the development of high-end equipment manufacturing industry and new energy sources, the market field has further expanded, and the requirements for the mechanical properties of silicon nitride ceramic materials used with them have become more stringent. The traditional method of improving the mechanical properties of silicon nitride is mainly to improve the heat treatment process to promote grain growth and densification, but in fact, the optimization of process parameters does not significantly improve the mechanical properties of silicon nitride, and the process parameters are difficult to strictly control.

[0003] The existing technology improves the mechanical properties of silicon nitride by introducing second phase particles, which refine the grains and increase the resistance to crack propagation. However, the size of the introduced second phase particles is difficult to control, the particles are unevenly dispersed, and the wettability of the second phase particles and the silicon nitride matrix is ​​poor, resulting in poor hardness performance of the formed silicon nitride. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the problems in the prior art such as the difficulty in controlling the size of the second phase particles, the uneven dispersion of the particles, and the poor wettability of the second phase particles with the silicon nitride matrix, which lead to the poor hardness performance of silicon nitride, thereby providing a method for preparing high-hardness silicon nitride ceramics.

[0005] To this end, the present invention provides a method for preparing high-hardness silicon nitride ceramics, comprising the following steps: S1, mixing a silicon source, a titanium source and a carbon source, and sintering them in a nitrogen atmosphere to obtain an intermediate; S2, mixing the intermediate and a sintering aid, and sintering them to obtain a high-hardness silicon nitride ceramic.

[0006] In some embodiments, the molar ratio of the titanium source to the silicon source in step S1 is 0.5-8:100.

[0007] Preferably, the molar ratio of the titanium source to the silicon source is 1-4:100, and more preferably, the molar ratio of the titanium source to the silicon source is 2:100.

[0008] The molar ratio of the total molar amount of the titanium source and the silicon source to the carbon source is 1:2-6.

[0009] In some of the embodiments, the sintering step in step S1 specifically includes increasing the temperature to 1200-1250°C at a heating rate of 5-10°C / min, maintaining for 0.5-2h, increasing the temperature to 1350-1400°C at a heating rate of 2-5°C / min, maintaining for 10-20h, reducing the temperature to 1200-1250°C at a cooling rate of 2-6°C / min, maintaining for 0.5-1.5h, and reducing the temperature to 25-35°C at a cooling rate of 2-6°C / min.

[0010] In some embodiments, the sintering pressure in step S1 is 0.12-0.16 MPa.

[0011] In some of the embodiments, the step S1 further comprises a step of decarbonizing the intermediate, and the specific step comprises calcining the intermediate at 650-700° C. for 1-4 hours.

[0012] In some of the embodiments, the silicon source, titanium source and carbon source are mixed by ball milling, the rotation speed of the ball milling is 300-360 rpm, and the ball milling time is 12-36 hours.

[0013] In some of the embodiments, the mass ratio of the intermediate to the sintering aid in step S2 is 45-49:1-5.

[0014] In some of the embodiments, the sintering step in step S2 specifically includes increasing the temperature to 1200-1250°C at a heating rate of 2-6°C / min, maintaining for 0.5-1.5h, increasing the temperature to 1650-1850°C at a heating rate of 2-6°C / min, maintaining for 2-10h, reducing the temperature to 1200-1250°C at a cooling rate of 2-8°C / min, maintaining for 0.5-1.5h, and reducing the temperature to 25-35°C at a cooling rate of 3-8°C / min.

[0015] In some of the embodiments, the specific step of mixing the intermediate and the sintering aid includes mixing the silicon nitride of the intermediate and the sintering aid by ball milling in the presence of a solvent, the ball milling speed is 300-400 rpm, and the ball milling time is 12-36 hours.

[0016] In some of the embodiments, after the intermediate and the sintering aid are mixed and before sintering, the mixed slurry is dried and cold isostatically pressed. The drying temperature is 80-90°C, the drying time is 8-12h, and the cold isostatic pressing pressure is 150-300Mpa.

[0017] In some embodiments, the carbon source includes at least one of carbon powder or sugars. Preferably, the sugar includes at least one of monosaccharides, disaccharides and polysaccharides, more preferably, the monosaccharide includes glucose, the disaccharide is sucrose, and the polysaccharide includes starch.

[0018] In some embodiments, the silicon source includes at least one of silica gel and silicate. Preferably, the silicate includes organic silicate and inorganic silicate, more preferably, the organic silicate includes tetraethyl orthosilicate, and more preferably, the inorganic silicate is sodium silicate.

[0019] In some of the embodiments, the titanium source includes at least one of inorganic titanium and organic titanium. Preferably, the titanium source includes at least one of titanium dioxide, tetrabutyl titanate, ethyl titanate, and isopropyl titanate.

[0020] In some embodiments, the sintering aid includes a metal oxide.

[0021] Preferably, the sintering aid includes at least one of yttrium oxide, aluminum oxide, magnesium oxide, ytterbium oxide, lanthanum oxide and scandium oxide.

[0022] The technical solution of the present invention has the following advantages: The present invention provides a method for preparing a high-hardness silicon nitride ceramic, comprising the following steps: S1, mixing a silicon source, a titanium source and a carbon source, sintering in a nitrogen atmosphere to obtain an intermediate; S2, mixing and sintering the intermediate and a sintering aid to obtain a high-hardness silicon nitride ceramic. The present invention obtains an intermediate containing titanium nitride and silicon nitride by sintering a silicon source, a titanium source and a carbon source in a nitrogen atmosphere. When the intermediate and the sintering aid are sintered to form silicon nitride, a crystal phase transition from α to β phase occurs, and the in-situ synthesized TiN can be embedded between the formed silicon nitride grains. On the one hand, the present invention improves the uniformity of the distribution of TiN in silicon nitride grains by in-situ synthesis, which not only achieves the improvement of mechanical properties, but also improves the uniformity of the color of the sintered body. On the other hand, the generation of TiN particles and silicon nitride grains occurs synchronously, which improves the interface bonding force between silicon nitride and the second phase, further improves the interface wettability, and at the same time enhances the interface bonding strength between silicon nitride and the second phase, thereby achieving the improvement of the hardness of silicon nitride.

[0023] The preparation method provided by the present invention has simple steps, low cost and pure material components, and is conducive to the large-scale production of high-hardness silicon nitride. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 is a microscopic morphology of the silicon nitride ceramic material obtained in Example 1 of the present invention; Figure 2 This is a microscopic morphology of the silicon nitride ceramic material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0027] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0028] Example 1 This embodiment provides a method for preparing high-hardness silicon nitride ceramics, and the specific steps and parameters are as follows: (1) Weigh silicon dioxide (purity 99.99%, 500 nm), titanium dioxide (purity 99.99%, 300 nm) and high-purity carbon powder (purity 99.99%, 50 nm), wherein the molar ratio of titanium dioxide to silicon dioxide is 1:50, and the molar ratio of the sum of the moles of silicon dioxide and titanium dioxide to the high-purity carbon powder is 1:3; The above powders are added into the drum mill in proportion and mixed by ball milling to obtain mixed powder. Silicon nitride balls are selected as grinding balls. The mass ratio of powder to grinding balls is 3:1. The ball milling mixing time is 24 hours at a rotation speed of 300 rpm.

[0029] (2) The mixed powder is placed in a silicon nitride crucible and placed in a nitriding furnace for sintering. The entire sintering process is divided into four stages. In the first stage, the temperature is increased at a heating rate of 5°C / min to 1200°C and kept at 1200°C for 1 hour; In the second stage, the temperature was raised at a heating rate of 3°C / min to 1400°C and kept at 1400°C for 12 h; In the third stage, the temperature was lowered to 1200°C at a rate of 2°C / min and kept at 1200°C for 0.5h; In the fourth stage, the temperature was lowered to 25°C at a cooling rate of 3°C / min.

[0030] The entire sintering process was carried out in a nitrogen environment with the pressure maintained at 0.12 MPa.

[0031] (3) The sintered powder is placed in a decarbonization furnace and calcined at 700°C for 2 hours in an air environment to remove the carbon in the powder.

[0032] After the carbon removal treatment, the carbon content in the powder is less than 0.08wt%.

[0033] (4) Take the powder, aluminum oxide and yttrium oxide obtained in step (3), add the above raw materials and grinding balls into a ball mill, pour alcohol (75 vol% ethanol solution), and ball mill at 300 rpm for 16 hours to obtain a slurry, wherein the mass ratio of the powder, aluminum oxide and yttrium oxide obtained in step (3) is 93:3:4, and the mass ratio of the above raw materials, alcohol and grinding balls is 1:1.5:5.

[0034] (5) Place the slurry in a vacuum drying oven for 10 hours at 80°C and dry it to obtain a powder.

[0035] (6) A φ35 mm silicon nitride blank disc is pressed by an automatic tablet press, and the silicon nitride blank disc is cold isostatically pressed at a cold isostatic pressure of 160 MPa.

[0036] (7) Place the green ball after cold isostatic pressing in a graphite crucible, sprinkle boron nitride powder on it, and sinter it in an atmosphere pressure sintering furnace. The sintering is divided into four stages: In the first stage, the temperature was raised to 1200 °C at a heating rate of 6 °C / min and kept at 1200 °C for 1 h; In the second stage, the temperature was raised to 1750°C at a heating rate of 3°C / min and kept at 1750°C for 2 h; In the third stage, the temperature was lowered to 1200°C at a cooling rate of 3°C / min and kept at 1200°C for 30 min; In the fourth stage, the temperature was lowered to 25°C at a cooling rate of 5°C / min.

[0037] A silicon nitride ceramic material with high hardness is obtained.

[0038] The microscopic morphology of the silicon nitride ceramic material obtained in this example is shown in Figure 1 It can be seen that the TiN on the silicon nitride formed by in-situ growth of TiN (the white dots in the figure are TiN) is evenly distributed and the color of the sintered body is uniform.

[0039] Example 2 This embodiment provides a method for preparing high-hardness silicon nitride ceramics, and the specific steps and parameters are as follows: (1) Weigh silicon dioxide (purity 99.99%, 500 nm), titanium dioxide (purity 99.99%, 300 nm) and high-purity carbon powder (purity 99.99%, 50 nm), wherein the molar ratio of titanium dioxide to silicon dioxide is 1:25, and the molar ratio of the sum of the moles of silicon dioxide and titanium dioxide to the high-purity carbon powder is 1:3; The above powders are added into the drum mill in proportion and mixed by ball milling to obtain mixed powder. Silicon nitride balls are selected as grinding balls. The mass ratio of powder to grinding balls is 3:1. The ball milling mixing time is 24 hours at a speed of 320 rpm.

[0040] (2) Place the mixed powder into a silicon nitride crucible and place it in a nitriding furnace for sintering. The entire sintering process is divided into four stages: In the first stage, the temperature was raised at a heating rate of 6 °C / min to 1200 °C and kept at 1200 °C for 1 h; In the second stage, the temperature was raised to 1400°C at a heating rate of 3°C / min and kept at 1400°C for 13 h; In the third stage, the temperature was lowered to 1200°C at a rate of 3°C / min and kept at 1200°C for 0.5h; In the fourth stage, the temperature was lowered to room temperature at a cooling rate of 3°C / min.

[0041] The entire sintering process was carried out in a nitrogen environment with the pressure maintained at 0.12 MPa.

[0042] (3) The sintered powder is placed in a decarbonization furnace and calcined at 700°C for 3 hours in an air environment to remove the carbon in the powder.

[0043] After the carbon removal treatment, the carbon content in the powder is less than 0.08wt%.

[0044] (4) Take the powder, aluminum oxide and yttrium oxide obtained in step (3), add the above raw materials and grinding balls into a ball mill, pour alcohol (75 vol% ethanol solution), and ball mill for 16 hours to obtain a slurry, wherein the mass ratio of the powder, aluminum oxide and yttrium oxide obtained in step (3) is 95:2:3, and the mass ratio of the above raw materials, alcohol and grinding balls is 1:1.5:5.

[0045] (5) Place the slurry in a vacuum drying oven for 10 hours at 85°C and dry it to obtain a powder.

[0046] (6) A φ35 mm silicon nitride blank disc is pressed by an automatic tablet press, and the silicon nitride blank disc is cold isostatically pressed at a cold isostatic pressure of 180 MPa.

[0047] (7) Place the green ball after cold isostatic pressing in a graphite crucible, sprinkle boron nitride powder on it, and sinter it in an atmosphere pressure sintering furnace. The sintering is divided into four stages: In the first stage, the temperature was raised to 1200 °C at a heating rate of 6 °C / min and kept at 1200 °C for 1 h; In the second stage, the temperature was raised to 1750°C at a heating rate of 3°C / min and kept at 1750°C for 2 h; In the third stage, the temperature was lowered to 1200°C at a cooling rate of 3°C / min and kept at 1200°C for 30 min; In the fourth stage, the temperature was lowered to room temperature at a cooling rate of 5°C / min.

[0048] A silicon nitride ceramic material with high hardness is obtained.

[0049] Example 3 This embodiment provides a method for preparing high-hardness silicon nitride ceramics, and the specific steps and parameters are as follows: (1) Weigh silicon dioxide (purity 99.99%, 500 nm), titanium dioxide (purity 99.99%, 300 nm) and high-purity carbon powder (purity 99.99%, 50 nm), wherein the molar ratio of titanium dioxide to silicon dioxide is 3:50, and the molar ratio of the sum of the moles of silicon dioxide and titanium dioxide to the high-purity carbon powder is 1:3; The above powders are added into the drum mill in proportion and mixed by ball milling to obtain mixed powder. Silicon nitride balls are selected as grinding balls. The mass ratio of powder to grinding balls is 3:1. The ball milling mixing time is 24 hours at a rotation speed of 360 rpm.

[0050] (2) Place the mixed powder into a silicon nitride crucible and place it in a nitriding furnace for sintering. The entire sintering process is divided into four stages: In the first stage, the temperature was raised at a heating rate of 8 °C / min to 1200 °C and kept at 1200 °C for 1 h; In the second stage, the temperature was raised at a heating rate of 3°C / min to 1400°C and kept at 1400°C for 15 h; In the third stage, the temperature was lowered to 1200°C at a rate of 5°C / min and kept at 1200°C for 1h; In the fourth stage, the temperature was lowered to room temperature at a cooling rate of 3°C / min.

[0051] The entire sintering process was carried out in a nitrogen environment with the pressure maintained at 0.13 MPa.

[0052] (3) The sintered powder is placed in a decarbonization furnace and calcined at 700°C for 4 hours in an air environment to remove the carbon in the powder.

[0053] After the carbon removal treatment, the carbon content in the powder is less than 0.08wt%.

[0054] (4) Take the powder, aluminum oxide and yttrium oxide obtained in step (3), add the above raw materials and grinding balls into a ball mill, pour in alcohol, and ball mill for 16 hours to obtain a slurry, wherein the mass ratio of the powder, aluminum oxide and yttrium oxide obtained in step (3) is 97:1:2, and the mass ratio of the above raw materials, alcohol and grinding balls is 1:1.5:5.

[0055] (5) Place the slurry in a vacuum drying oven at 90°C for 10 hours and dry it to obtain a powder.

[0056] (6) A φ35 mm silicon nitride blank disc is pressed by an automatic tablet press, and the silicon nitride blank disc is cold isostatically pressed at a cold isostatic pressure of 200 MPa.

[0057] (7) Place the green ball after cold isostatic pressing in a graphite crucible, sprinkle boron nitride powder on it, and sinter it in an atmosphere pressure sintering furnace. The sintering is divided into four stages: In the first stage, the temperature was raised to 1200 °C at a heating rate of 6 °C / min and kept at 1200 °C for 1 h; In the second stage, the temperature was raised to 1750°C at a heating rate of 3°C / min and kept at 1750°C for 2 h; In the third stage, the temperature was lowered to 1200°C at a cooling rate of 3°C / min and kept at 1200°C for 30 min; In the fourth stage, the temperature was lowered to room temperature at a cooling rate of 5°C / min.

[0058] A silicon nitride ceramic material with high hardness is obtained.

[0059] Example 4 This embodiment provides a method for preparing high-hardness silicon nitride ceramics, and the specific steps and parameters are as follows: (1) Weigh tetraethyl orthosilicate (purity 99.99%), tetrabutyl titanate (purity 99.99%) and high-purity glucose powder (purity 99.99%), wherein the molar ratio of tetrabutyl titanate to tetraethyl orthosilicate is 0.5:100, and the molar ratio of the sum of the moles of tetraethyl orthosilicate and tetrabutyl titanate to the high-purity glucose powder is 1:6; The above powders and solutions are added into a drum mill in proportion for ball milling to obtain mixed powder. Silicon nitride balls are used as grinding balls. The mass ratio of powder to grinding balls is 3:1. The ball milling mixing time is 12 hours at a rotation speed of 360 rpm.

[0060] (2) Place the mixed powder into a silicon nitride crucible and place it in a nitriding furnace for sintering. The entire sintering process is divided into four stages: In the first stage, the temperature was raised to 1250°C at a heating rate of 10°C / min and kept at 1250°C for 0.5h; In the second stage, the temperature was raised to 1350°C at a heating rate of 2°C / min and kept at 1350°C for 10 h; In the third stage, the temperature was lowered to 1250°C at a rate of 6°C / min and kept at 1250°C for 1.5 h; In the fourth stage, the temperature was lowered to 35°C at a cooling rate of 6°C / min.

[0061] The entire sintering process was carried out in a nitrogen environment with the pressure maintained at 0.16 MPa.

[0062] (3) The sintered powder is placed in a decarbonization furnace and calcined at 650°C for 4 hours in an air environment to remove the carbon in the powder.

[0063] After the carbon removal treatment, the carbon content in the powder is less than 0.08wt%.

[0064] (4) Take the powder, magnesium oxide and ytterbium oxide obtained in step (3), add the above raw materials and grinding balls into a ball mill, pour alcohol (75 vol% ethanol solution), and ball mill at 360 rpm for 36 hours to obtain a slurry, wherein the mass ratio of the powder, aluminum oxide and yttrium oxide obtained in step (3) is 90:5:5, and the mass ratio of the above raw materials, alcohol and grinding balls is 1:1.5:5.

[0065] (5) Place the slurry in a vacuum drying oven for 12 hours at 80°C and dry it to obtain a powder.

[0066] (6) A φ35 mm silicon nitride blank disc is pressed by an automatic tablet press, and the silicon nitride blank disc is cold isostatically pressed at a cold isostatic pressure of 300 MPa.

[0067] (7) Place the green balls after cold isostatic pressing in a graphite crucible and sinter them in an atmosphere pressure sintering furnace. The sintering process is divided into four stages: In the first stage, the temperature was raised to 1250 °C at a heating rate of 2 °C / min and kept at 1250 °C for 0.5 h; In the second stage, the temperature was raised to 1650°C at a heating rate of 2°C / min and kept at 1650°C for 10 h; In the third stage, the temperature was lowered to 1250°C at a cooling rate of 2°C / min and kept at 1250°C for 1.5 h; In the fourth stage, the temperature was lowered to 25°C at a cooling rate of 3°C / min.

[0068] A silicon nitride ceramic material with high hardness is obtained.

[0069] Example 5 This embodiment provides a method for preparing high-hardness silicon nitride ceramics, and the specific steps and parameters are as follows: (1) Weigh silica gel (purity 99.99%), ethyl titanate (purity 99.99%) and high-purity sucrose powder (purity 99.99%), wherein the molar ratio of ethyl titanate to silica gel is 2:25, and the molar ratio of the sum of the moles of silica gel and ethyl titanate to the high-purity sucrose powder is 1:2; The above powders and solutions are added to a drum mill in proportion for ball milling to obtain mixed powder. Silicon nitride balls are used as grinding balls. The mass ratio of powder to grinding balls is 3:1. The ball milling mixing time is 12 hours at a rotation speed of 300 rpm.

[0070] (2) Place the mixed powder into a silicon nitride crucible and place it in a nitriding furnace for sintering. The entire sintering process is divided into four stages: In the first stage, the temperature was raised at a heating rate of 5 °C / min to 1200 °C and kept at 1200 °C for 2 h; In the second stage, the temperature was raised at a heating rate of 2°C / min to 1400°C and kept at 1400°C for 20 h; In the third stage, the temperature was lowered to 1200°C at a rate of 2°C / min and kept at 1200°C for 0.5h; In the fourth stage, the temperature was lowered to 30°C at a cooling rate of 3°C / min.

[0071] The entire sintering process was carried out in a nitrogen environment with the pressure maintained at 0.14 MPa.

[0072] (3) The sintered powder is placed in a decarbonization furnace and calcined at 700°C for 1 hour in an air environment to remove the carbon in the powder.

[0073] After the carbon removal treatment, the carbon content in the powder is less than 0.08wt%.

[0074] (4) Take the powder, lanthanum oxide and scandium oxide obtained in step (3), add the above raw materials and grinding balls into a ball mill, pour alcohol (75 vol% ethanol solution), and ball mill at 300 rpm for 12 hours to obtain a slurry, wherein the mass ratio of the powder, lanthanum oxide and scandium oxide obtained in step (3) is 98:1:1, and the mass ratio of the above raw materials, alcohol and grinding balls is 1:1.5:5.

[0075] (5) Place the slurry in a vacuum drying oven for 8 hours at 90°C and dry to obtain a powder.

[0076] (6) A φ35 mm silicon nitride blank disc is pressed by an automatic tablet press, and the silicon nitride blank disc is cold isostatically pressed at a cold isostatic pressure of 150 MPa.

[0077] (7) Place the green ball after cold isostatic pressing in a graphite crucible, sprinkle boron nitride powder on it, and sinter it in an atmosphere pressure sintering furnace. The sintering is divided into four stages: In the first stage, the temperature was raised to 1200 °C at a heating rate of 2 °C / min and kept at 1200 °C for 1.5 h; In the second stage, the temperature was raised to 1850 °C at a heating rate of 6 °C / min and kept at 1850 °C for 2 h; In the third stage, the temperature was lowered to 1250°C at a cooling rate of 8°C / min and kept at 1250°C for 1 h; In the fourth stage, the temperature was lowered to 25°C at a cooling rate of 8°C / min.

[0078] A silicon nitride ceramic material with high hardness is obtained.

[0079] Comparative Example 1 This comparative example provides a method for preparing high-hardness silicon nitride ceramics, and the specific steps and parameters are as follows: (1) Weigh silicon nitride, aluminum oxide, yttrium oxide and TiN, add the above raw materials and grinding balls into a ball mill, pour in alcohol, and ball mill for 16 hours to obtain a slurry, wherein the mass ratio of silicon nitride, aluminum oxide and yttrium oxide is 93:3:4, the amount of TiN added is 0.3wt% of the total mass of silicon nitride, aluminum oxide and yttrium oxide, and the mass ratio of the total mass of silicon nitride, aluminum oxide, yttrium oxide and TiN, alcohol and grinding balls is 1:1.5:5.

[0080] (2) Place the slurry in a vacuum drying oven at 80°C for 10 hours and dry it to obtain a powder.

[0081] (3) An automatic tablet press is used to press a φ35 mm silicon nitride blank disc, and the silicon nitride blank disc is cold isostatically pressed at a cold isostatic pressure of 160 MPa.

[0082] (4) The green balls after cold isostatic pressing are placed in a graphite crucible, sprinkled with boron nitride powder, and placed in an atmosphere pressure sintering furnace for sintering. The sintering is divided into four stages. In the first stage, the temperature is increased to 1200°C at a heating rate of 6°C / min and kept at 1200°C for 1 h. In the second stage, the temperature is increased to 1750°C at a heating rate of 3°C / min and kept at 1750°C for 2 h. In the third stage, the temperature is reduced to 1200°C at a cooling rate of 3°C / min and kept at 1200°C for 30 min. In the fourth stage, the temperature is cooled to room temperature at a cooling rate of 5°C / min.

[0083] Silicon nitride ceramic material is obtained.

[0084] The microscopic morphology of the silicon nitride ceramic material obtained in this comparative example is shown in Figure 2 , it can be seen that TiN is unevenly distributed on silicon nitride ( Figure 2 The white dots in the middle represent TiN), and the color of the sintered body is not uniform.

[0085] Comparative Example 2 This comparative example provides a method for preparing high-hardness silicon nitride ceramics, and the specific steps and parameters are as follows: (1) Weigh silicon nitride, aluminum oxide, yttrium oxide and TiN, add the above raw materials and grinding balls into a ball mill, pour in alcohol, and ball mill for 16 hours to obtain a slurry, wherein the mass ratio of silicon nitride, aluminum oxide and yttrium oxide is 95:2:3, the amount of TiN added is 0.6wt% of the total mass of silicon nitride, aluminum oxide and yttrium oxide, and the mass ratio of the total mass of silicon nitride, aluminum oxide, yttrium oxide and TiN, alcohol and grinding balls is 1:1.5:5.

[0086] (2) Place the slurry in a vacuum drying oven at 80°C for 10 hours and dry it to obtain a powder.

[0087] (3) An automatic tablet press is used to press a φ35 mm silicon nitride blank disc, and the silicon nitride blank disc is cold isostatically pressed at a cold isostatic pressure of 160 MPa.

[0088] (4) The green balls after cold isostatic pressing are placed in a graphite crucible, sprinkled with boron nitride powder, and placed in an atmosphere pressure sintering furnace for sintering. The sintering is divided into four stages. In the first stage, the temperature is increased to 1200°C at a heating rate of 6°C / min and kept at 1200°C for 1 h. In the second stage, the temperature is increased to 1750°C at a heating rate of 3°C / min and kept at 1750°C for 2 h. In the third stage, the temperature is reduced to 1200°C at a cooling rate of 3°C / min and kept at 1200°C for 30 min. In the fourth stage, the temperature is cooled to room temperature at a cooling rate of 5°C / min.

[0089] Silicon nitride ceramic material is obtained.

[0090] Experimental example The density and hardness of the silicon nitride ceramic materials prepared in Examples 1-5 and Comparative Examples 1-2 were tested, and the results are shown in Table 1.

[0091] The density is tested by the Archimedes drainage method, and the hardness is tested in accordance with the GB / T 16534-2009 method.

[0092] Table 1 Performance determination of silicon nitride ceramic materials

[0093] According to the data in Table 1, compared with the silicon nitride ceramics formed by titanium nitride, silicon nitride and sintering aids in Comparative Examples 1 and 2, the present invention uses a silicon source, a titanium source and a carbon source to sinter in a nitrogen atmosphere to obtain an intermediate containing titanium nitride and silicon nitride. While the intermediate and the sintering aid are sintered to form silicon nitride, a crystal phase transformation occurs to form a silicon nitride ceramic with good density and hardness.

[0094] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing high-hardness silicon nitride ceramics, characterized in that: The following steps are included: S1, mixing a silicon source, a titanium source and a carbon source, and sintering them in a nitrogen atmosphere to obtain an intermediate; S2, mixing the intermediate and the sintering aid, and sintering to obtain high-hardness silicon nitride ceramics.

2. The method for preparing high-hardness silicon nitride ceramics according to claim 1, characterized in that: The molar ratio of the titanium source to the silicon source in step S1 is 0.5-8:100; and / or, The molar ratio of the total molar amount of the titanium source and the silicon source to the carbon source is 1:2-6.

3. The method for preparing high hardness silicon nitride ceramics according to claim 2, characterized in that: The sintering step in step S1 specifically includes increasing the temperature to 1200-1250°C at a heating rate of 5-10°C / min, maintaining for 0.5-2h, increasing the temperature to 1350-1400°C at a heating rate of 2-5°C / min, maintaining for 10-20h, reducing the temperature to 1200-1250°C at a cooling rate of 2-6°C / min, maintaining for 0.5-1.5h, and reducing the temperature to 25-35°C at a cooling rate of 2-6°C / min; and / or, The sintering pressure in step S1 is 0.12-0.16 MPa.

4. The method for preparing high hardness silicon nitride ceramics according to claim 3, characterized in that: The step S1 further comprises a step of decarbonizing the intermediate, and the specific steps include calcining the intermediate at 650-700° C. for 1-4 hours; and / or, The silicon source, titanium source and carbon source are mixed by ball milling, the rotation speed of the ball mill is 300-360rpm, and the ball milling time is 12-36h.

5. The method for preparing high-hardness silicon nitride ceramics according to claim 4, characterized in that: In step S2, the mass ratio of the intermediate to the sintering aid is 45-49:1-5.

6. The method for preparing high-hardness silicon nitride ceramics according to claim 5, characterized in that: The sintering step in step S2 specifically includes increasing the temperature to 1200-1250°C at a heating rate of 2-6°C / min, maintaining for 0.5-1.5h, increasing the temperature to 1650-1850°C at a heating rate of 2-6°C / min, maintaining for 2-10h, reducing the temperature to 1200-1250°C at a cooling rate of 2-8°C / min, maintaining for 0.5-1.5h, and reducing the temperature to 25-35°C at a cooling rate of 3-8°C / min.

7. The method for preparing high-hardness silicon nitride ceramics according to claim 1, characterized in that: The specific step of mixing the intermediate and the sintering aid includes mixing the silicon nitride of the intermediate and the sintering aid by ball milling in the presence of a solvent, the rotation speed of the ball milling is 300-400 rpm, and the ball milling time is 12-36 hours.

8. The method for preparing high-hardness silicon nitride ceramics according to claim 7, characterized in that: After the intermediate and the sintering aid are mixed, before sintering, the mixed slurry is dried and cold isostatically pressed. The drying temperature is 80-90° C. and the drying time is 8-12 hours. The cold isostatic pressing pressure is 150-300 MPa.

9. The method for preparing high-hardness silicon nitride ceramics according to claim 1, characterized in that: The carbon source comprises at least one of carbon powder or sugar; and / or, The silicon source comprises at least one of silica gel and silicate; and / or, The titanium source comprises at least one of organic titanium and inorganic titanium; and / or, The sintering aid includes a metal oxide.

10. The method for preparing high-hardness silicon nitride ceramics according to claim 9, characterized in that: The titanium source includes at least one of titanium dioxide, tetrabutyl titanate, ethyl titanate, and isopropyl titanate; and / or, The silicate comprises at least one of an organic silicate and an inorganic silicate; and / or, The organic silicate comprises tetraethyl orthosilicate; and / or, The inorganic silicate is sodium silicate; and / or, The sugar includes at least one of monosaccharide, disaccharide and polysaccharide; and / or, The sintering aid includes at least one of yttrium oxide, aluminum oxide, magnesium oxide, ytterbium oxide, lanthanum oxide, and scandium oxide.

Citation Information

Patent Citations

  • Method for producing carbon titanium nitride and titanium nitride powder through quick nitridation

    CN108424147A

  • High-toughness low-resistance silicon nitride ceramic and preparation method thereof

    CN112479721A

  • Directionally grown titanium carbonitride crystal, preparation method and application thereof

    CN113151889A

  • Silicon carbide reinforced silicon nitride ceramic and preparation method thereof

    CN113548903A

  • Wear-resistant silicon nitride ceramic cutter material and preparation method thereof

    CN113603493A